VIGOR DAYA SIMPAN UMBI BAWANG MERAH (Allium ascallonicum L.) VARIETAS PALASA DAN LEMBAH PALU TERHADAP BERBAGAI KONDISI SIMPAN - Priyantono, Eko; Ete, Andi; Anton, Adrianton (AGROTEKBIS, 2013)
Onion (Allium  ascallonicum L.) is a potential commodity especially in the city of Palu. Shallots Central Sulawesi than as a food flavoring agent very suitable for use as a feedstock fried onions. The purpose of this study was to determine the exact condition on the variety store Palasa and Palu valley are able to maintain the vigor of onion bulbs save energy. The expected usefulness of this study was to determine how the storage of onion bulbs to maintain vigor remains high shelf. This study used a split plot design consisting of: (1) local onion varieties as main plots (V1) = Onion Varieties Palasa, (V2) = Onion Varieties Palu valley, (2) The condition is saved as a subplot (K1) = room air conditioning (temperature 20-250 C), (K2) = space room (temperature> 28-300 C), (K3) = free air space (temperature> 300 C).  The results showed that the varieties Palasa produce speed germination and germination times better. Storage on the condition of free air space produces germination, speed of germination and germination time and the dry weight is higher. Varieties Palu valley and Palasa has vigor shelf high on the condition of free air space savings, although in an air conditioned room with a temperature of 250 C is still showing good vigor.